2013
DOI: 10.1158/1078-0432.ccr-12-0274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathways: PI3K Pathway Targets in Triple-Negative Breast Cancers

Abstract: The triple-negative breast cancer (TNBC) subtype, defined clinically by the lack of estrogen, progesterone, and Her2 receptor expression, accounts for 10% to 15% of annual breast cancer diagnoses. Currently, limited therapeutic options have shown clinical benefit beyond cytotoxic chemotherapy. Defining this clinical cohort and identifying subtype-specific molecular targets remain critical for new therapeutic development. The current era of high-throughput molecular analysis has revealed new insights into these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…Pharmacological inhibition of both the ERK and AKT signaling pathways, but not either pathway alone, induces TNBC cell death [10, 21]. We previously showed that CIB1 depletion impaired both ERK and AKT activation, leading to significant cell death in MDA-MB-468 cells [10].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological inhibition of both the ERK and AKT signaling pathways, but not either pathway alone, induces TNBC cell death [10, 21]. We previously showed that CIB1 depletion impaired both ERK and AKT activation, leading to significant cell death in MDA-MB-468 cells [10].…”
Section: Resultsmentioning
confidence: 99%
“…of adjacent normal tissue, and high-grade HCMV-LA was detected in only 3%, 11%, and 5%, Approximately 10-15% of BCs are classified as TNBC, for which treatment options are very limited 40 . Out of 10 TBNC cases in our study, 7 (70%) had high-grade expression of HCMV-IE.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, as elegantly discussed in several publications (2-4), these canine cancers, which bridge a gap between traditional rodent models and human clinical trials, can significantly speed up new anticancer drug development. For example, for drugs targeting the PI3K pathway (48) (Figure 7C), their efficacy, toxicity, dosage and schedule can be more accurately evaluated through clinical trials with canine patients, before entering human clinical trials. This will significantly reduce the cost and accelerate the drug discovery process.…”
Section: Discussionmentioning
confidence: 99%